Life cycle assessment and sensitivity analysis of carbon emissions in full depth reclamation with portland cement and conventional pavement repair - Haiwei Zhang; Qingqing Zhang; Chuangdan Luo; Ning Liu; Ke Wang (Scientific Reports)
Abstract Full-depth reclamation with Portland cement (FDR-PC) is a pavement rehabilitation technology that has garnered significant attention and research interest due to its ability to fully utilize existing pavement materials in situ and address deep structural issues within the pavement. This paper evaluates the advantages of FDR-PC in terms of carbon emission compared to traditional asphalt pavement rehabilitation technologies. Firstly, under the same service life conditions, the structural configurations of asphalt pavements were designed using 3D-Move Analysis for three different technologies: removal and reconstruction, cold central plant recycling, and FDR-PC. Subsequently, carbon emission models were established based on the life cycle assessment (LCA) method and the construction processes, allowing for a comparison of carbon emissions and energy consumption among the three technologies. Finally, a sensitivity analysis was conducted to assess the impact of various factors on carbon emissions during the FDR-PC construction process. The results indicate that in terms of carbon emissions from the pavement base layer, FDR-PC accounts for 92% and 90% of those produced by removal and reconstruction and cold central plant recycling, respectively, while its energy consumption is 60% and 70% of the latter two technologies. Notably, during the transportation phase, FDR-PC demonstrates carbon emissions and energy consumption levels at merely 4% each compared to conventional removal and reconstruction, and 6% each relative to cold central plant recycling. The sensitivity analysis further reveals that the cement content is the most influential factor affecting the carbon emissions of FDR-PC.